PEMANFAATAN INDEKS KUALITAS UDARA (IKU) SEBAGAI INDIKATOR PERGERAKAN EKONOMI JAWA TIMUR DI TENGAH PANDEMI COVID-19 - Joko Ade Nursiyono; Ima Sartika Dewi (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
The Covid-19 pandemic that hit East Java has affected various aspects in life including health, social and economic aspects. The government imposed an emergency public activity restriction (PPKM darurat) policy as an effort to control the spread of Covid-19. As a result of these restrictions, the economy in East Java is declined. This study aims to predict economic recovery in East Java after the emergency public activity restriction (PPKM darurat) policy based on changes in the air quality index before and after the implementation of emergency public activity restriction (PPKM darurat). The data in this study were obtained through big data by web-scrapping. Using the mean difference test and Mac Nemar test, this study shows that there is a significant change in air quality index status from healthy to unhealthy air quality in districts/cities in East Java after the easing of emergency public activity restriction (PPKM darurat).